TYPE 1NEUROFIBROMATOSIS AND EFFECTS ON THE STOMATOGNATIC SYSTEM - Cardoso, InÃƒÂªs Lopes; Noronha, Anariely (Journal of Medical Biomedical and Applied Sciences, 2018)
Neurofibromatosis is a systemic hereditary disorder that mainly affects the skin and nervous system. It was identified for the first time by Friedrich Von Recklinghausen, being called the Von Recklinghausen syndrome. Some of the clinical symptoms can be visible since birth, however, most of them start to show up during childhood and adolescenceand, in women, phenotype becomes evident during pregnancy, due to the severe hormonal changesthat occur. The goal of this research was to understand the way type I neurofibromatosis can affect the oral cavity and how the dental doctor can help. For that, several papers were selected from the search on the websites Pubmed, Elsevier andUptoDateusing the following keywords: neurofibromatosis, oral health, neurofibroma, oral cancer, GTP, type 1 neurofibromatosis. Concerning clinical features at the oral cavity, more than one fourth of patients with this disorder can show neurofibromas in the mouth, usually isolated.Phenotype can include increased fungiform papillae, head and neck polyps, nodules in the posterior portionof the back of the tongue, dental mobility caused by lesionsin the gingival-dental-alveolar complex, changes in the number of teeth, molar retention, dental calculus, aplasia of the second bottom molarsandadvanced periodontal disease. Bone changes can be present like subperiosteal erosion, hyperplasia, hypoplasia, dysplasia in the wings of the sphenoidandshortsize.Concerning therapeutic strategies, some studies suggest that proteins of the mTOR pathway (mammalian target of rapamycin) can be the target for therapyof this disease in case of malignant transformation.